2010
DOI: 10.1016/j.jml.2010.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Real-time processing of gender-marked articles by native and non-native Spanish speakers

Abstract: Three experiments using online processing measures explored whether native and non-native Spanish-speaking adults use gender-marked articles to identify referents of target nouns more rapidly, as shown previously with 3-year-old children learning Spanish as L1 (Lew-Williams & Fernald, 2007). In Experiment 1, participants viewed familiar objects with names of either the same or different grammatical gender while listening to Spanish sentences referring to one object. L1 adults, like L1 children, oriented to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
161
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(178 citation statements)
references
References 74 publications
(101 reference statements)
14
161
3
Order By: Relevance
“…This would be consistent with the idea of more "shallow," that is, less syntactically driven processing (cf. the "good enough" account by Ferreira, 2003) in L2 compared with native speakers (see Clahsen & Felser, 2006) and with behavioral studies suggesting that L2 speakers may not make use of word gender (Lew-Williams & Fernald, 2010;Scherag, Demuth, Rösler, Neville, & Röder, 2004;Guillelmon & Grosjean, 2001). However, the recategorization of trials in terms of subjective correctness for the L2 learners showed a different picture: Subjectively unexpected determiners triggered an ERP response on the subsequent noun.…”
Section: Gender Agreement Condition and The Role Of Incorrect Subjectmentioning
confidence: 92%
“…This would be consistent with the idea of more "shallow," that is, less syntactically driven processing (cf. the "good enough" account by Ferreira, 2003) in L2 compared with native speakers (see Clahsen & Felser, 2006) and with behavioral studies suggesting that L2 speakers may not make use of word gender (Lew-Williams & Fernald, 2010;Scherag, Demuth, Rösler, Neville, & Röder, 2004;Guillelmon & Grosjean, 2001). However, the recategorization of trials in terms of subjective correctness for the L2 learners showed a different picture: Subjectively unexpected determiners triggered an ERP response on the subsequent noun.…”
Section: Gender Agreement Condition and The Role Of Incorrect Subjectmentioning
confidence: 92%
“…I will not try to distinguish among these models; instead, I will assume a rather general approach, mainly based on ideas put forward by researchers working in a connectionist tradition (e.g., Elman, 1991;MacDonald, 2013;MacDonald, Pearlmuttter, & Seidenberg, 1994;Tabor & Tanenhaus, 1999). Based on a lifetime of exposure to their native language, native speakers of a language have learned to associate certain words, word categories, syntactic frames and rules, building a database of relative frequencies of occurrence and associations.…”
Section: Factors Modulating Predictionmentioning
confidence: 99%
“…Another example of the effect of frequency information is the subcategorization bias of verbs. Scholars working in the constraint-based lexicalist framework have provided ample evidence that the relative frequencies of subcategorization frames and argument types of a verb affect processing preferences (e.g., Boland, Tanenhaus, Garnsey, & Carlson, 1995;MacDonald et al, 1994;Stowe, Tanenhaus, & Carlson, 1991;Wilson & Garnsey, 2009). This information is also used in a predictive manner, as shown by Boland (2005).…”
Section: Frequency Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, results have been mixed, even when the same L2 is examined. Lew-Williams and Fernald (2010) and Grüter et al (2012) did not find gender anticipation or facilitation effects for intermediate and advanced…”
Section: Eye-tracking and Grammatical Processingmentioning
confidence: 71%